Modifying the electrical properties of Ba0.85Ca0.15Zr0.1Ti0.9O3ceramics by the nanocrystals-induced method - Piewpan Parjansri (2018)
Copyright © 2016 American Scientific Publishers All rights reserved. This work investigated the phase formation and electrical properties of Ba0.85Ca0.15Zr0.1Ti0.9O3(BCZT) prepared by the nanocrystals-induced method. We prepared the nanocrystals or seeds by the molten salt method, using CaCO3and TiO2oxides as starting materials. The CaTiO3seeds showed a pure perovskite phase, and we obtained a particle size of ∼300 nm. After that, we mixed the CT seed with the starting powders of Ba0.85Ca0.15Zr0.1Ti0.9O3ceramic, prepared by the solid state reaction method. Results found that all ceramics showed a pure perovskite phase. The density values were in the range of 5.51 to 5.64 g/cm3, while relative density values were 96-99%. We measured the electrical properties (including dielectric, ferroelectric, and piezoelectric properties) as a function of CaTiO3seed content. We obtained the highest dielectric constant (εr∼ 4239) and lowest dielectric loss (tan δ ∼ 0.010) measured at room temperature from a sample with x = 0.08. Moreover, the BCZT doped with CaTiO3seed (x = 0.10) showed the highest values for the piezoelectric charge coefficient (d33) ∼ 477 pC/N, piezoelectric voltage coefficient (g33) ∼ 16 × 10-3Vm/N, and thickness mode electromechanical coupling (kt) ∼ 51.18%. Results suggested that CaTiO3-seeds enhanced the electrical properties of the BCZT ceramic using low calcination temperatures and with less dwelling time.